2019
DOI: 10.3991/ijet.v14i01.9458
|View full text |Cite
|
Sign up to set email alerts
|

On the Effects of Computer-assisted Teaching on Learning Results Based on Blended Learning Method

Abstract: With the rapid development of the computer network technology, the blended learning method based on computer-assisted teaching has also been booming. This paper analyzes the connotations of blended learning and the architecture and main functions of the Moodle system by using research methods such as litera-ture analysis, development and research method and sample survey method and then establishes a blended learning model based on the Moodle platform. Then, with the course of C Programming Language as an exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…Students are thus provided with different means for acquiring essential literacy skills and interacting with content. Similarly, some authors [76] praised blended learning models based on the Moodle platform, reporting their usefulness for furthering teaching effects and potential as a reference for the innovation of models and methodologies. In this line, a study analyzing students' perception of the quality of two BL educational courses, one using Moodle and another not [77], found that the students preferred to participate mainly in collaborative activities.…”
Section: Implications For Participantsmentioning
confidence: 99%
“…Students are thus provided with different means for acquiring essential literacy skills and interacting with content. Similarly, some authors [76] praised blended learning models based on the Moodle platform, reporting their usefulness for furthering teaching effects and potential as a reference for the innovation of models and methodologies. In this line, a study analyzing students' perception of the quality of two BL educational courses, one using Moodle and another not [77], found that the students preferred to participate mainly in collaborative activities.…”
Section: Implications For Participantsmentioning
confidence: 99%
“…To develop the teaching -learning environment, I chose Moodle (Modular Object-Oriented Dynamic Learning Environment) open-source freeware software, which is freely usable under a GPL license, so it can be customized with own, individual development and idea [19]. When choosing a framework, besides ensuring student liaison, it was an important consideration that it supports the production of e-books (with text, graphics, spreadsheets, images, sound and video), compatible with the SCORM (Sharable Content Object Reference Model) standard, by which well structured, spectacular educational materials can prepared.…”
Section: 2mentioning
confidence: 99%
“…Bi and Shi analyzed the connotations of blended learning and the architecture and main functions of the Moodle system and established a blended learning model based on the Moodle platform. The results of an investigation of the design and implementation of C Programming Language show that Moodle platforms can improve teaching effects and serve as a reference for the innovation of teaching models and methods (Bi & Shi, 2018 emerging technology with analytic processes provided a particular advantage in transforming the pattern of information in the innovative environment of online resources to enhance learning resources (Miftachul, Andino, Pardimin, Maragustam, & Roslee, 2018). Xia et al researched a method to design and apply 3D visualization resources in teaching scenes and showed that 3D visualization resources can effectively improve students' interest in learning and help students understand knowledge (Xia, Li, & Zhou, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%